El fashion film, una herramienta publicitaria para expresar la personalidad de marca. Estudio de caso: fashion drama (2018)
The development of this research joins theoretical aspects relevant around the industry of fashion, advertising, audiovisual production and more specifically the Fashion film, as well as a product communicative that makes up part of the advertainment and that is able to express the personality of a brand. Goes to define the fashion film, their characteristics and their variations taking as a point of departure for the analysis, the case of three fashion films that are part of a series of audiovisual products fashion entitled "Fashion drama" of Vogue magazine, Spain. The research is conducted and its development through the development of a methodology that seeks to distinguish the components of the fashion film and to know the perception of professionals linked to the fashion industry in the face of this topic